Transição Mínima E Música Em Dissolução: Estudo Sobre A Música De Alban Berg Sob A Crítica De Theodor Adorno - Serrano Junior, Luiz Antonio [UNIFESP] (2018)
This Work Intends To Study The Philosophical And Musical Relations In Alban Berg's Oeuvre, Not Only From Theodor Adorno's Critic Texts As Also From His Personal Relationship To The Composer, His Friend And Teacher, And With His Music, Seen By Adorno As The Most Successful In Conciliating The Objectivity Of The Constructive Method To The Inventive Subjectivity Of The Artist. Our Work Develops In Three Stages " Always Relating Adorno's Theorizations To Berg's Music " Which Are: The Discussion About Musical Language Within The Compositional Landscape Of The Early 20th Century; The Musical Analysis As A Legitimate Way Of Aesthetic Evaluation, According To Adorno's Criteria Of Truth Content [Wahrheitsgehalt], In Replacement To The Ancient Categories Of Beautiful Or Sublime; And The Compositional Methods Of Alban Berg, The Master Of Minimal Link, As Its Implications Along His Oeuvre.